Problems of Muslim Society in Southeast Asia: A Study of the Impact of Online Games from an Islamic Law Perspective - Jusoh Yusoff, Amir Fazlim; Djawas, Mursyid (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
One of the problems of Islamic law in Southeast Asia and even the world today is the emergence of online games in Muslim society. Therefore, concerns have arisen about the game, how it impacts Muslim society, whether it is in accordance with Islamic law or not. This study aims to examine the impact of online games on Muslim society and how Islamic law views it. This qualitative study applies content analysis related to Islamic legal analysis. Reference terms have been compiled as a guideline, taken from the main opinions of three schools of thought, namely al-Syafi'iyyah, al-Malikiyyah, and al-Hanabilah according to their main references. Interviews with sharia experts provide information on the assessment of this third item. Finally, Islamic legal analysis determines the decision on these items related to justice according to the opinions of the previously mentioned schools of thought with their reference terms. This study reveals that the mystery box and unlimited purchase features in dare and esports games are compared to the requirements of justice according to sharia. Online games are not only contrary to Islamic law because they contain elements of gambling, fraud and speculation. Online games can also have negative impacts on the perpetrators such as psychological, health, economic, social and mental disorders, so that the perpetrators can behave abnormally both physically and psychologically. In addition, it also goes against Malay cultural values ​​that uphold strong Islamic teachings in society. This study also recommends that the government strictly control and grant permits to institutions that create online games that are more educational and beneficial for people in Southeast Asia, especially Malaysia and Indonesia.